Pertimbangan Hakim Terhadap Kasus Perceraian yang Diajukan oleh Pihak Suami Sebagai Penggugat Dikarenakan Istri Melarikan Diri (Studi Putusan Nomor: 83/Pdt. G/2024/PN.Tjk) - Pratama, Dimas Disa; Hakim, Lukmanul (Journal of Law, Education and Business, 2025)
Divorce is the dissolution of a marriage by a judge's decision or the demands of one of the parties to the marriage. It is the same as leaving another party without permission and a valid reason or other things beyond one's capabilities. Things that can cause divorce can vary, from incompatibility, domestic violence, to infidelity. The problem in this research is the factors causing the Plaintiff to file a lawsuit for Divorce Based on Decision Number 83/Pdt.G/2024/PN.TJK. and the judge's consideration in granting the divorce suit was because the wife ran away based on Decision Number 83/Pdt.G/2024/PN.Tjk. The research method used in this thesis research is a normative juridical approach and an empirical approach. Secondary data is data obtained through literature studies (library research) such as literature books and scientific works related to research problems. Secondary data consists of 3 (three) legal materials, namely, primary, secondary and tertiary legal materials. Prime data is data obtained from research results in the field directly on the research object (field research) which is carried out by direct observation and interviews regarding the object in writing this thesis. Furthermore, the Judge's consideration in granting the divorce was based on the fact that the wife had abandoned the marriage, as stipulated in Decision Number 83/Pdt.G/2024/PN.Tjk, in accordance with Article 39 of Law Number 1 of 1974, as amended by Law Number 16 of 2019 on Marriage, which states in conjunction with Article 19(f) of Government Regulation Number 9 of 1975 concerning the implementation of Law Number 1 of 1974 on Marriage, that divorce may occur due to reasons including continuous disputes and conflicts between husband and wife, with no hope of reconciliation in the household.